The Łódź-Zielona Góra publication Selected texts from the history of the Polish language (2015) edited by Marek Cybulski in comparison with Polish, Slavic and non-Slavic chrestomathies - Lewaszkiewicz, Tadeusz (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The object of this article is a review of Selected texts… (2015) edited by Marek Cybulski in comparison with Polish and selected Slavic and non-Slavic chrestomathies. The considerable importance of this work in Polish linguistics is evidenced by a number of factors: the timespan (covering both earliest and recent texts), the exceptional (even astounding) variety of text styles and genres, well-edited informational notes preceding the texts, and appended glossaries. However, the most important and original feature of this publication are the comments that follow texts, as they reflect the deep theoretical linguistic knowledge of the authors. This is currently the largest and best chrestomathy in historical Slavic linguistics and likely in historical non-Slavic linguistics as well.